A importância do crescimento econômico local na escolha do chefe do Executivo no Brasil - Fernandes, Ivan Filipe de Almeida Lopes (2017)
The motives for choosing the government's chief executive are of vital importance in a democratic society. In this article, evidence is presented of how local economic growth in the last year of government has a positive impact on the percentage of votes obtained by the incumbent in a population sample of Brazilian municipalities, with data of the presidential and municipal elections of 2000 to 2010. Real GDP growth of the city is used as a measure of local economic growth to test the hypothesis that voters in a municipality tend to reward incumbents and their candidates, if they had good economic performance in the last year of their mandate. The hypothesis is based on the economic theory of voting, suggesting that incumbents are more likely to win re-election, or elect their successor, when the economy is good. Panel and Multilevel models are used to detail the effects and the impact of economic growth in the proportion of votes obtained by the incumbent. The multilevel analysis was used in order to better explore existing heterogeneity in the economic voting phenomenon and thereby infer how economic growth effects may vary among parties, the federation units, constituency and other variables.